Model Sikap Penggunaan dan Minat Beli: Analisis Persepsi Kemudahan, Persepsi Kemanfaatan dan Kepercayaan (Studi Kasus Fitur Instagram Shop dan Media Sosial Instagram) - Ali, Hapzi; Fatmawati M, Inayatullah (Jurnal Siber Multi Disiplin, 2023)
This study aims to analyze the effect of perceived convenience, perceived usefulness and trust on attitudes to use and the influence of perceived convenience, perceived usefulness and trust on purchase intention. The population in this study are internet users who have done online shopping but have never made an online purchase transaction on Instagram and are domiciled in the Jakarta area. The number of samples used is based on the number of indicators at an error rate of 5%, namely 180. The survey was conducted using a questionnaire and then data analysis using Partial Least Square (PLS). The results showed that perceived usefulness and trust had a significant effect on attitudes towards use and purchase intention using the Instagram Shop feature on Instagram Social Media and perceived ease of use had no effect on usage attitudes and purchase intentions using the Instagram Shop feature on Instagram Social Media.